Колебания скорости потока сепарируемой зерновой смеси на цилиндрическом виброрешете - Ольшанский, В. П.; Ольшанский, Станислав Васильевич (НТУ "ХПИ", 2010)
Розглянуто гармонічні коливання швидкості потоку зернової суміші, яка рухається по внутрішній поверхні вертикального циліндричного решета вібросепаратора. Використовуючи теорію вібророзрідження зернового шару, аналітичний розв’язок граничної задачі гідродинаміки представлено за допомогою функцій Кельвіна. Побудовано також наближений розв’язок задачі для спрощеного розрахунку швидкості потоку сепарованої суміші та продуктивності решета в виробничих умовах.

Harmonically vibrations of velocity of a flow a grain mix are considered, driven on an internal surface of a vertical cylindrical sieve of vibroseparator. Using the theory vibroliquefaction of a grain layer, the analytical solution of a regional problem of hydrodynamics is submitted with the help of Kelvin functions. The approximate solution of a problem for the simplified account of velocity of a flow separating of a mix and productivity sieve under production conditions is constructed also.
Keywords: вибросепаратор; математическое моделирование; кольцевой слой; вибровязкость смеси